Sex Steroid Hormones as a Balancing Factor in Oral Host Microbiome Interactions - Cornejo Ulloa, Pilar; Krom, Bastiaan P.; van der Veen, Monique H. (Frontiers in Cellular and Infection Microbiology, 2021)
Sex steroid hormones (SSH) are cholesterol-derived molecules. They are secreted into saliva and enter the oral cavity, triggering physiological responses from oral tissues, with possible clinical implications, such as gingival inflammation and bleeding. SSH and hormonal changes affect not only oral host cells but also oral microorganisms. Historically, most research has focused on the effect of hormonal changes on specific bacteria and yeasts. Recently a broader effect of SSH on oral microorganisms was suggested. In order to assess the role of SSH in host-microbe interactions in the oral cavity, this review focuses on how and up to what extent SSH can influence the composition and behavior of the oral microbiome. The available literature was reviewed and a comprehensive hypothesis about the role of SSH in host-microbiome interactions is presented. The limited research available indicates that SSH may influence the balance between the host and its microbes in the oral cavity.